2019
DOI: 10.1021/acsaelm.9b00351
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-Scale Fabrication of 42° Rotated Y-Cut LiTaO3-on-Insulator (LTOI) Substrate for a SAW Resonator

Abstract: A high-performance filter is the key component in 5G communication. A surface acoustic wave (SAW) resonator fabricated on a piezoelectric thin film instead of piezoelectric bulk substrate can achieve a higher quality factor (Q) and a lower temperature coefficient of frequency (TCF).Here we performed the fabrication of 4 in. 42°rotated Y-cut LiTaO 3 -on-insulator (LTOI) hybrid substrate applied for the surface acoustic wave (SAW) radio-frequency (RF) resonators. This heterogeneous substrate combining a submicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
(56 reference statements)
0
33
0
Order By: Relevance
“…The process flow for transferring LT thin films) First, the LT sample was implanted at 75 kev H + , and through direct wafer bonding, the single-crystal-level LT thin film was Transferred to a Si substrate, post-annealing at 400 °C further improved the crystalline quality, and then a 30 nm damaged layer was removed by an optimized chemical mechanical polishing (CMP) process, resulting in a significant increase in the blistered surface roughness of the LT film from 12 nm. It was reduced to 0.2 nm, and finally a 350 MHZ single-port surface acoustic wave resonator was designed using the prepared LTOI (LiTaO 3 -on-insulator) substrate [ 79 ].…”
Section: Saw Filter Technologymentioning
confidence: 99%
“…The process flow for transferring LT thin films) First, the LT sample was implanted at 75 kev H + , and through direct wafer bonding, the single-crystal-level LT thin film was Transferred to a Si substrate, post-annealing at 400 °C further improved the crystalline quality, and then a 30 nm damaged layer was removed by an optimized chemical mechanical polishing (CMP) process, resulting in a significant increase in the blistered surface roughness of the LT film from 12 nm. It was reduced to 0.2 nm, and finally a 350 MHZ single-port surface acoustic wave resonator was designed using the prepared LTOI (LiTaO 3 -on-insulator) substrate [ 79 ].…”
Section: Saw Filter Technologymentioning
confidence: 99%
“…It has been reported that InP heterojunction bipolar transistors (HBTs) can be integrated on Si materials platforms within silicon fabrication facilities [59], as presented in Figure 8(c). Based on the ion-cutting technology [60][61][62][63], the researchers realized different kinds of wafer scale heterogeneous integration materials, e.g., GaAs/Si, InP/Si, LiTaO 3 /Si, LiNbO 3 /Si, SiC/Si, and Ga 2 O 3 /SiC, as shown in Figure 8(d).…”
Section: Cross-dimensional Heterogeneous Integrationmentioning
confidence: 99%
“…Ion slicing process is a feasible and versatile approach for the transfer of single‐crystalline films, which was first proposed by Bruel in 1995, [ 18 ] and has been applied to the mass production of Si‐on‐Insulator (SOI) wafers for years. It has also been successfully extended to the transfer of functional single‐crystalline films onto heterogeneous substrates in waferscale, such as InP‐on‐Si, [ 19 ] SiC‐on‐Si, [ 20 ] Ga 2 O 3 ‐on‐SiC, [ 21 ] and LiTaO 3 ‐on‐Si. [ 22 ] In recent years, lithium niobate, an artificial crystal with exceptional electro‐optical, pyroelectric, ferroelectric, and piezoelectric properties, has regained widespread attention.…”
Section: Introductionmentioning
confidence: 99%